2011
DOI: 10.1186/1749-8546-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Harmine activates intrinsic and extrinsic pathways of apoptosis in B16F-10 melanoma

Abstract: BackgroundHarmine is a beta-carboline alkaloid from the plant Peganum harmala. Previous studies found that harmine inhibited metastasis of B16F-10 melanoma cells. This study aims to elucidate the role of harmine in apoptosis of B16F-10 cells.MethodsB16F-10 melanoma cells were treated in the presence and absence of harmine in vitro. Morphological changes, cell cycle and expression of various pro and anti- apoptotic genes were analyzed for the study of apoptosis.ResultsMorphological observation and DNA laddering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 35 publications
(41 reference statements)
2
48
0
Order By: Relevance
“…Protein expression of MCL1 and C-FLIP are modulated by NF-ĸB activation in cancer (12). Han et al showed that silencing NF-ĸB reduced C-FLIP expression and enhanced TRAIL-induced apoptosis in glioblastoma cells (24 TRAIL in glioblastoma cells (6). We confirmed such effects by finding that NF-ĸB inhibitor reduced NF-ĸB activation and protein expression of MCL1 and C-FLIP in U-87 MG cells (Figure 3).…”
Section: Discussionsupporting
confidence: 74%
“…Protein expression of MCL1 and C-FLIP are modulated by NF-ĸB activation in cancer (12). Han et al showed that silencing NF-ĸB reduced C-FLIP expression and enhanced TRAIL-induced apoptosis in glioblastoma cells (24 TRAIL in glioblastoma cells (6). We confirmed such effects by finding that NF-ĸB inhibitor reduced NF-ĸB activation and protein expression of MCL1 and C-FLIP in U-87 MG cells (Figure 3).…”
Section: Discussionsupporting
confidence: 74%
“…Harmine has been reported to have antidepressantlike actions in rodents [2] . Harmine possesses anxiolytic, behavioral effects and anti-tumor potential both in vitro and in vivo [5] . Harmine has high inhibitory affinity of DYRK1A kinase activity, suggesting that harmine could alter tau phosphorylation [6] .…”
Section: Pharmacological Evidence Of Harminementioning
confidence: 99%
“…The role of harmine in apoptosis of B16F-10 cells was investigated. Harmine activates both intrinsic and extrinsic pathways of apoptosis and regulates some transcription factors and pro-inflammatory cytokines [5] . The in vivo anti-angiogenic activity of harmine was studied using B16F-10 melanoma cells in C57BL/6 mice.…”
Section: Effect Of Harmine Against Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These in vitro studies have shown that harmine, b-carbolines alkaloid have more activity (Lamchouri et al, 2010). The harmine and β-carbolines alkaloid are highly cytotoxic and significantly inhibited tumor cell growth with apoptotic effect (Hamsa & Kuttan, 2011). This study showed that harmine significantly inhibited tumor nodule formation in the lung tissue and decreased various biochemical parameters associated with lung metastasis.…”
Section: Fatima Lamchourimentioning
confidence: 78%